Neutrality Law in the Age of Digitalization: An Analysis of the Russia-Ukraine Conflict - Mellisa Towadi; Zamroni Abdussamad; Anis Bajrektarevic; Lisnawaty W Badu; Waode Mustika (Universitas Negeri Semarang, 2023)
This article aims to describe the application of the concept of neutrality law in the current era with the contamination of digitalization. The main problem refers to the intervention of third countries or neutral states in the Russian conflict v. Ukraine, then questioned the existence of neutrality law in the era of digitalization. The method used is a normative juridical method with a statute approach analyzed qualitatively and descriptively. The results show that validity is needed in determining the attitude of third countries or neutral states that intervene with belligerents (Russia/Ukraine). The determination of the validity is based on the scale of the intervention provided by the third country. Validity refers to the 1907 Hague Convention and the UN Charter, which generally outlines violations of territorial sovereignty and international law. So, in conclusion, the concept of open access, broad and immeasurable digitalization, cannot be avoided in the conflict between Russia and Ukraine. This does not necessarily become a justification because the essence of the principle of neutrality and intervention is very different; the two cannot be combined unless a violation of international law indicates one. So basically, neutrality law can no longer be the primary regulation to control the attitude of a neutral state but requires new norms that shape the attitude of a neutral state so that it can be used as international customary law.